The Association Between the Levels of Thyroid Hormones and Peripheral Nerve Conduction in Patients with Type 2 Diabetes Mellitus - Zhu, Fan-Fan; Yang, Li-Zhen (Experimental and Clinical Endocrinology & Diabetes, 2018)
Background Type 2 diabetes has an underlying pathology with thyroid dysfunction. However, few studies have investigated the association between thyroid hormones and diabetic peripheral neuropathy. Our aim was to evaluate the relationship between thyroid hormones and electrophysiological properties of peripheral nerves in type 2 diabetes.Patients and Methods The medical records of 308 patients with type 2 diabetes were enrolled in this study. Subjects stratified by sex were divided into subgroups based on the diagnosis of nerve conduction study. The nerve conduction parameters were separately described with the spectrum of thyroid hormones. Multivariate regression models to analyze the potential links between thyroid hormones and nerve conduction parameters.Results The serum free triiodine thyronine levels between normal and abnormal nerve conduction groups were statistically different in total (4.55±0.65 vs 4.37±0.63, P<0.05) and female diabetic patients (4.46±0.50 vs 4.14±0.57, P<0.01). Moreover, the summed amplitude and velocity Z score of female and male increased with free triiodine thyronine levels (P<0.05). Sex-specific binary logistic regression models showed that free triiodine thyronine levels were associated with decreased odds of abnormal nerve conduction diagnosis (odds ratio [95%CI]=0.151[0.047-0.186]) and low tertile of summed amplitude Z score (odds ratio [95%CI]=0.283[0.099-0.809]) in female. In total patients, free triiodine thyronine level was negatively associated with odds of abnormal nerve conduction (odds ratio [95%CI]=0.436 [0.226-0.842]), low tertile of summed velocity (odds ratio [95%CI]=0.44[0.226-0.858]) and amplitude (odds ratio [95%CI]=0.436[0.227-0.838) Z score.Conclusions Serum free triiodine thyronine level is associated with nerve conduction in diabetes. Low free triiodine thyronine may be a potential risk for diabetic peripheral neuropathy.
Keywords: Type 2 diabetes mellitus; Diabetic peripheral neuropathy; Nerve conduction study; Thyroid hormones; Free triiodine thyronine